Total Occlusion in Three Coronary Main Vessels, How Could the Patient Survive?: A Case Report - Aljauza, Muhammad; Hernugrahanto, Aldhi Pradana; Firmansyah, Radian Tommy; Shafira, Aisya Ayu; Putri, Kezia Warokka; Anandita, Faizal Ablansah (Journal of Neonatal Surgery, 2025)
Coronary artery disease (CAD) is one of the most common diseases in developed countries and has a high morbidity and mortality. ST-elevation myocardial infarction (STEMI) accounts for approximately 30% of all acute coronary syndrome (ACS) cases. Total occlusion refers to a complete blockage of a coronary artery, this blockage significantly reduces or completely stops blood flow to the heart muscle. Chronic Total Occlusion (CTO) is defined as a 100% occlusion of a coronary artery that has been present for at least 3 months. CTO can be found in various clinical situations, such as ACS, or discovered during evaluation with imaging modalities when there is a complaint of chest pain, or when the patient undergoes angiography when undergoing valve replacement surgery, or surgery for congenital heart disease. Management of patients with CTO remains a challenge, so more detailed examination is needed to achieve the best results